Coregonus autumnalis ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Coregonus autumnalis (Pallas, 1776). Arctic Cisco. To 64 cm (25 in) TL (Berg 1948). Arctic coasts from Siberia west to White Sea; Point Lay, Alaska (Craig and Schmidt 1985) to Ramussen Basin, Nunuvut, Canada (Reist in Coad and Reist 2018). Close to shore in estuaries (Mecklenburg et al. 2002). Anadromous and landlocked populations. ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 52, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...